TANGGUNG JAWAB DIREKTUR UTAMA PT GORGA DUMA SARI TERHADAP PERISTIWA PIDANA PERUSAKAN LINGKUNGAN HIDUP (STUDI PUTUSAN MAHKAMAH AGUNG NO.1203 K/PID.SUS.LH/2016) - MUHAMMAD IQBAL (PREMISE LAW JURNAL, 2019)
Dosen pembimbing:1. Prof. Dr. Syafruddin Kalo, SH, MHum2. Dr. T. Keizerina Devi A, SH, CN, MHum3. Dr. Mahmud Mulyadi, SH, MHum Article 1, point 5 of Law No. 40/2007 on Limited Liability Company States, Directors are the organs of a company. They have the authority and liability for its management and interest according to its goal. They represent it in and outside the Court. The Supreme Court’s Ruling No. 1203K/Pdt.Sus.LH/2016 in the case of Jonni Sihotanng as the President Director of PT. Gorga Duma Sari who gives orders and leads the activity is found guilty of committing environmental damage criminal act. This research discussed the liability of the President Director of PT. Gorga Duma Sari for committing environmental damage criminal act.